Modeling, stability and the activity assessment of glutathione reductase from Streptococcus Thermophilus; Insights from the in-silico simulation study. (December 2019) - Gholampour-Faroji, Nazanin; Farazmand, Razieh; Hemmat, Jafar; Haddad-Mashadrizeh, Aliakbar
Graphical abstract: Highlights: Glutathione reductase of Streptococcus thermophilus is characterized and modeled via in-silico . The constructed model of Glutathione reductase is stable at 400 K. CYS40 and CYS45 are specified as the active site residues of this enzyme. Antioxidant capability of the enzyme is supported via its affinity to the corresponding ligands. Abstract: Antioxidant enzymes (AEs) are the main parts of the natural barriers of the body which deactivate the oxidant factors. To discover and understand their structures and function will deserve a deeper investigation. Accordingly, as an AE of probiotic strains, glutathione reductase of Streptococcus thermophilus (GRst), is characterized and modeled by in-silico methods. The investigation indicated the physicochemical properties of the enzyme and estimated its half-life of being more than 10 h. The analysis revealed that the enzyme is composed of 86 strands, 123 helices, and 241 random coils. Homology modeling of the GRst led to the construction of the enzyme's 3D model that 62% of which is analogous to the glutathione reductase of Escherichia Coli (GRec), and which is qualitatively high in terms of Molpdf, ERRAT, Verify-3D and Ramachandran scores. Moreover, the structural stability of the model was substantiated within 10 and 20 ns at 400 and 300 K, respectively. Interestingly, these data showed that the enzyme is more stable than GRec at 400 K. In other words, the active cavity of the constructed model is characteristic of 38 amino acid residues within 4 Å around the NADPH and GSSG as corresponding ligands of GRst. Noteworthy, herein is the fact that, CYS40 and CYS45 are specified as the active site residues of this enzyme. Furthermore, the interaction assays of the model support its antioxidant capability which is even more than that of GRec. In general, these data provide a new model of AEs being inclusive of high antioxidant capacity and thermostability.